2005
DOI: 10.1128/jvi.79.19.12554-12565.2005
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated Rabies Virus Activates, while Pathogenic Rabies Virus Evades, the Host Innate Immune Responses in the Central Nervous System

Abstract: Rabies virus (RV) induces encephalomyelitis in humans and animals. However, the pathogenic mechanism of rabies is not fully understood. To investigate the host responses to RV infection, we examined and compared the pathology, particularly the inflammatory responses, and the gene expression profiles in the brains of mice infected with wild-type (wt) virus silver-haired bat RV (SHBRV) or laboratory-adapted virus B2C, using a mouse genomic array (Affymetrix). Extensive inflammatory responses were observed in ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
206
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(223 citation statements)
references
References 54 publications
15
206
1
1
Order By: Relevance
“…In immune cells, we have shown the ability of CRMP2 to bind vimentin and tubulin (Vincent et al, 2005) parenchyma (Kleine and Benes, 2006;Lane et al, 2000;Lee et al, 2004;Liu et al, 2000;Ransohoff et al, 2003). Chemokines are expressed at high levels in the virus infected CNS, as it is the case after RABV infection (Baloul and Lafon, 2003;Roy et al, 2007;Wang et al, 2005).…”
Section: -Discussionmentioning
confidence: 99%
“…In immune cells, we have shown the ability of CRMP2 to bind vimentin and tubulin (Vincent et al, 2005) parenchyma (Kleine and Benes, 2006;Lane et al, 2000;Lee et al, 2004;Liu et al, 2000;Ransohoff et al, 2003). Chemokines are expressed at high levels in the virus infected CNS, as it is the case after RABV infection (Baloul and Lafon, 2003;Roy et al, 2007;Wang et al, 2005).…”
Section: -Discussionmentioning
confidence: 99%
“…Like most viruses, RABV has developed a strategy to counteract the antiviral effect of the type I IFN response (23,34,40,41,55,56). Despite these mechanisms, IFN, chemoattractive, and inflammatory responses in the RABV-infected NS are far from abrogated, and RABV successfully infects the NS (28,58).In this study, we investigate to what extent the innate immune response in the NS is important for the efficiency of RABV, immunoevasive strategy, and pathogenesis. To disturb the innate immune response and thus reveal its role in RABV infection, we infected a new mouse transgenic model that overexpresses LGP2 (LGP2 TG) with a neurovirulent RABV strain.…”
mentioning
confidence: 99%
“…Therefore, it is presumed that these amino acid differences can change the distribution of P protein in the This study showed that the virulent CE(NiP) strain with the P gene from Ni strain in the Ni-CE genome is less sensitive to type I IFN than is the avirulent Ni-CE strain, suggesting that the IFN sensitivity of the virus determined by the P gene is inversely related to pathogenicity of the virus. Interestingly, it has been reported that type I IFN is produced in the mouse brain in response to rabies virus infection (9,15). Therefore, it is thought that the different IFN sensitivities of Ni-CE and CE(NiP) strains influence their propagation efficiencies in vivo and result in their different pathogenicities.…”
mentioning
confidence: 99%